2011
DOI: 10.1007/978-3-642-23524-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Volatiles Mediating Information Between Bacteria and Plants

Abstract: At present, more than 400 volatiles are known to appear in bacterial headspace samples, but more are expected as more bacteria will be investigated and several identification technologies will be applied. A comprehensive list of bacteria and their respective effects on plants were presented. The volatiles emitted from Serratia plymuthica HRO-C48 and Stenotrophomonas maltophilia R3089 retarded leaf and root development of Arabidopsis thaliana starting at day 2 of cocultivation, while first signs of activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…Most research on VOC-mediated PGP has been performed on a few model plants and the mechanisms remain elusive for the most part, as reviewed by Bailly and Weisskopf (2012) and Wenke et al (2012b). By examining the interaction between N. attenuata and its naturally root-associated Bacillus sp B55, we uncovered a new mechanism of PGP: nutrient-driven PGP by the S-containing VOC DMDS, likely functioning by enhancing S availability and reducing the need for energy-demanding S assimilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research on VOC-mediated PGP has been performed on a few model plants and the mechanisms remain elusive for the most part, as reviewed by Bailly and Weisskopf (2012) and Wenke et al (2012b). By examining the interaction between N. attenuata and its naturally root-associated Bacillus sp B55, we uncovered a new mechanism of PGP: nutrient-driven PGP by the S-containing VOC DMDS, likely functioning by enhancing S availability and reducing the need for energy-demanding S assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…The PGP effects were largely attributed to two volatiles, namely, 3-hydroxybutan-2-one (acetoin) and 2,3-butanediol. Several other studies have examined bacterial bioactive volatile compounds that promote or suppress plant growth (Farag et al, 2006;Splivallo et al, 2007;Vespermann et al, 2007;Kai et al, , 2010Gutiérrez-Luna et al, 2010;Zou et al, 2010;Blom et al, 2011aBlom et al, , 2011bVelazquez-Becerra et al, 2011;Weise et al, 2012;Yu and Lee, 2013), but the underlying mechanisms of these effects remain largely unknown (Wenke et al, 2012b). Profiling studies in Arabidopsis seedlings provided the first insights into changes in the transcriptome and proteome elicited by exposure to bacterial VOCs (Zhang et al, 2007;Kwon et al, 2010) and revealed the importance of hormone signaling, particularly that of indole-3-acetic acid and abscisic acid (Zhang et al, 2007(Zhang et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…, 2010), but it appears that volatiles may play a role in plant–pathogen interactions. In dual‐culture, volatiles from both strains significantly decreased plant growth within 2–3 days, resulting in chlorosis and cell death (Wenke et al. , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…30 fungal species presently are known that emit complex volatile mixtures. The number of detectable volatiles in a species blend increases when various techniques are applied (e.g., dynamic headspace volatile capture in open and closed airflow systems, different trapping materials, solid phase microextraction (SPME), gas chromatography combined with mass spectrometry (GC/MS), proton transfer reaction/ mass spectrometry (PTR-MS), selected ion flow tube/mass spectrometry (SIFT-MS), secondary electron spray ionization/ mass spectroscopy (SESI-MS), as well as analytical chemistry) (summarized in Wenke et al, 2012). Furthermore, the effects of growth media and conditions on the emission spectra have to be considered (Fiddaman and Rossall, 1994;Blom et al, 2011a).…”
Section: Volatile Organic Compounds (>120 D) Emitted From Bacteria Anmentioning
confidence: 99%